Orienting India : - Dalmia, Vasudha (Three Essays Collective, 2003)
These three essays, by Vasudha Dalmia, explore the ways in which Europeans British colonialists and German philosophers and scholars appropriated Indian history, religious scholarship, and ritual practice to assert their own relationship to India and Indians, and even more so, their relationship to their own past and sense of present duty, right, and mission. In these European attempts to orient India to their own designs, justifications, and senses of moral worth, or enlightened thinking , Dalmia reveals the complex negotiations between Indian and British forms of knowledge and practice. In her study of the German thinkers, we see how cultural knowledge is not static but becomes a transaction between philosophers whose ideas of India form the basis of their own cultural values. In her evaluation of the British colonial project in India we see how the transactions between the British and high-caste Indians create new forms of power and realign social structures in the process. Contents: 1. Friedrich Max Mueller: Appropriation of the Vedic Past 2. Sanskrit Scholars and Pandits of the Old School: The Benares Sanskrit College and the Constitution of Authority in the Late Nineteenth Century 3. Sati in the Mirror of Post-Enlightenment Discourse: Parliamentary Papers on Widow Immolation, 1821-30